2010
DOI: 10.2217/fmb.10.135
|View full text |Cite
|
Sign up to set email alerts
|

Serum Helicobacter Pylori CagA Antibody As A Biomarker For Gastric Cancer in East-Asian Countries

Abstract: Aims-In east-Asian countries, while almost all Helicobacter pylori strains possess the cytotokine-associated gene A (CagA) gene, serum CagA antibody is not detected in some infected subjects. We aimed to clarify the association between anti-CagA antibody and gastric cancer in east-Asian countries.Materials & methods-We performed a meta-analysis of case-control studies with age-and sex-matched controls, which provided raw data in east-Asian countries.Results-Ten studies with a total of 4325 patients were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
52
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 57 publications
3
52
0
1
Order By: Relevance
“…Faecal-oral transmission is another route of infection related to sanitary conditions; water supply and sewage are considered important factors for H. pylori infection (Goh et al, 2011). After the Second World War, sanitary conditions improved in Japan and the prevalence of H. pylori infection decreased (Shiota et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Faecal-oral transmission is another route of infection related to sanitary conditions; water supply and sewage are considered important factors for H. pylori infection (Goh et al, 2011). After the Second World War, sanitary conditions improved in Japan and the prevalence of H. pylori infection decreased (Shiota et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, meta-analyses identified a significant relationship between vacA m-region genotype and cagA status and the development of diseases in Southeast Asia. Importantly, most of the H. pylori strains isolated from countries with high incidences of gastric cancer and anti-cagA antibody can be used as a biomarker for gastric cancer even in East Asian countries [55,[77][78].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there were no false positive results and therefore the Western-rCagA showed 100% specificity. This is also a good result for the rCagA of this study because the lack of specificity of antiCagA tests has been attributed in part to differences in the CagA antigens used (12,30).…”
Section: Discussionmentioning
confidence: 56%
“…However, the accuracy of the tests developed with this regard has been questioned because the results differed when they were used in different populations. It has been suggested that an important issue to this heterogeneity appeared to result from differences in the antigens used to detect anti-CagA antibodies (12). Consequently, new studies using the already existent CagA antigens, and/or some new design fragments of the cytotoxin, should be done to evaluate the reactivity of representative populations to different antigens.…”
Section: Discussionmentioning
confidence: 99%